Biological Control of Phytophthora palmivora Causing Root Rot of Pomelo Using Chaetomium spp. - Phung Manh Hung; Pongnak Wattanachai; Soytong Kasem; Supatta Poaim (My University, 2015)
Phytophthora diseases have become a major impediment in the citrus production in Thailand. In this study, an isolate of Phytophthora denominated as PHY02 was proven to be causal pathogen of root rot of Pomelo (Citrus maxima) in Thailand. The isolate PHY02 was morphologically characterized and identified as Phytophthora palmivora based on molecular analysis of an internal transcribed spacer rDNA sequence. This work also presents in vitro evaluations of the capacities of Chaetomium spp. to control the P. palmivora PHY02. As antagonists, Chaetomium globosum CG05, Chaetomium cupreum CC3003, Chaetomium lucknowense CL01 inhibited 50~61% mycelial growth, degraded mycelia and reduced 92~99% sporangial production of P. palmivora PHY02 in bi-culture test after 30 days. Fungal metabolites from Chaetomium spp. were tested against PHY02. Results showed that, methanol extract of C. globosum CG05 expressed strongest inhibitory effects on mycelial growth and sporangium formation of P. palmivora PHY02 with effective dose ED50 values of 26.5 µg/mL and 2.3 µg/mL, respectively. It is interesting that C. lucknowense is reported for the first time as an effective antagonist against a species of Phytophthora.
Keywords: Phytophthora palmivora; Chaetomium globosum; Root rot; Chaetomium; Phytophthora sojae; Plant Pathogens and Fungal Diseases